Entrepreneurship in a New Reality: GEM Slovenia 2020, Executive Summary (University of Maribor Press, 2021)
Entrepreneurship is the strongest driver of economic growth and development and has a very large impact on overall social development. The Global Entrepreneurship Monitor (GEM) has a history of 22 years of entrepreneurship research, with a special focus on the earliest stages, when business opportunities are perceived and individuals decide whether to engage in entrepreneurship. Their direct living environment, especially the prevailing cultural values, the company’s tendency to entrepreneurship and the orderliness of the business environment, have a great influence on the involvement of individuals in entrepreneurial activities. Accordingly, the conceptual framework of GEM is set, which enables the treatment of individuals and their attitude towards entrepreneurship, perception of entrepreneurship and involvement in the establishment and / or ownership and management of a company. With its help, we can therefore gain a deeper insight into national entrepreneurship and its characteristics and a more complete picture than can be provided by various statistical sources based solely on data obtained from existing companies.